Gerenciamento de geração de energia fotovoltaica residencial: uma análise de viabilidade - Reis, Sofia Barbosa dos (2019)
Brazil has privileges due to its extensive territory, added to the high and vast level of solar irradiation. Due to climatic variations and prolonged periods of drought, the consequence is the commitment of the production of electricity by the hydroelectric units of Brazil. This reality has attracted the attention of experts and scholars in the production of alternative electric energy for the characteristics of sustainability and high production of clean energy. Photovoltaic solar energy is in a growing situation of favorable cost, since it has the inputs that have fallen most in recent years. Investments in materials and methods required to implement them increase their viability. It presents general topics about solar energy, its application and a specific case study. We verified the inconsistencies in the management of materials and methods for this application and the feasibility of solar energy in this analyzed system of electricity production. And finally the recommendations for greater efficiency of the system.